Normative Effectiveness of Citizen Participation Scenarios in Colombia’s Legal Framework (2018)
Colombia’s Constitution of 1991 established citizen participation as one of the basic foundations for consolidating a Social State governed by the Rule of Law. Obeying this mandate, different participation instances were created that. According to the norm, these instances impel citizens to comply with this mandate. However, adequate mechanisms for the instances’ operation were not implemented. Faced with this situation, citizens autonomously created other non-formal instances in which the structuring elements of democratic participation may be identified. The present paper analyzes this tense situation by comparing normative effectiveness of both scenarios and seeks to identify in which of them is participation best represented, from the starting point of their foundation, including their active practice and control of political power. It is concluded that at present, formal scenarios are not adequate means for citizens to intervene assertively in the conformation, practice and control of political power, because it does not bring the necessary representativeness and legitimacy.